Visual hacking – why it matters and how to prevent it. Issue 7 (July 2019) - Barker, Peter
Abstract : To be truly comprehensive, security management strategies need to include prevention of visual security breaches – the ability to physically view and even photograph sensitive or confidential information. Visual privacy is either specified or implicit within a variety of regulations and industry-specific guidelines, and one area that is gaining considerable attention is preventing unauthorised viewing of sensitive or confidential information on digital screens.